A medallion for fortune and a virtù for pandora: Machado de Assis and Machiavelli - Soares, Daniel (2022)
This paper proposes a parallel between Machado de Assis and Machiavelli. Therefore, the paper was divided into four sections. In the first, two possible relationships between Machado de Assis and philosophy are presented: a reading of non-relationship and a reading of relationship. The second part discusses Margutti's interpretation of the relationship between Machado and philosophy. In the third stage, Maia Neto's reading of Machado's fiction is presented. In the fourth section, the parallel between Machado and Machiavelli is built based on the concepts presented in the previous steps. It ends with a discussion of the parallel.